Identification and initial treatment of involuntary psychogenic movement (conversion) disorder in a 25‐year‐old male patient - Andrew R. Hamm (Wiley, 2021)
Abstract Psychogenic movement disorders present a diagnostically challenging entity that is often frightening for patients. Differentiating movement disorders, providing clear explanations, and addressing underlying conditions with a multidisciplinary approach are essential to successful treatment.